TA’THĪR ISTIKHDĀM AL-WASĪLAH SMART APP CREATOR AL-QĀ’IM ‘ALĀ AL-MADKHAL AL-ITTIṢĀLĪ FĪ MAHĀRAT AL-KALĀM: تأثير استخدام الوسيلة منشئ التطبيقات الذكية القائم على المدخل الإتصالي في مهارة الكلام - Khairul Adam; Syofyan Hadi; Rahmawati; Lalu Iwandari (Tarbiyah Faculty of Ibrahimy University Ibrahimy University, Situbondo, Indonesia, 2026)
This study aimed to determine the effect of using Smart App Creator media based on the communicative approach on the Arabic speaking skill (maharah kalam) of eighth-grade students at Ma’had Al-Ma’arif Bukittinggi. The study was motivated by students’ low speaking proficiency, indicated by lack of confidence in communicating in Arabic, limited vocabulary mastery, difficulties constructing sentences, and dominance of conventional teaching methods that limited active speaking practice. This research employed a quantitative approach using a quasi-experimental design, specifically the Nonequivalent Control Group Design, involving 30 students as sample, consisting of 15 experimental and 15 control students. Data were collected through speaking tests before and after treatment and analyzed using normality tests, homogeneity tests, and Independent Samples t-Test with SPSS version 22. The findings revealed mean pretest scores of experimental and control classes were 56.27 and 54.20, while posttest scores increased to 85.87 and 79.07. Hypothesis testing showed significance value 0.005, lower than 0.05, indicating Smart App Creator had significant effect on students’ speaking skills. In conclusion, the integration of interactive digital media with communicative approach created more active, engaging, student-centered learning environment and improved Arabic speaking proficiency among students at junior secondary level and supports the effectiveness of Smart App Creator in enhancing speaking performance through structured practice, collaboration, and real-time communication activities that encourage learner participation and confidence in using Arabic in classroom interaction. This approach is recommended for Arabic language instruction improvement at Islamic junior secondary schools context.